Undifferentiated Intimal Sarcoma of the Visceral Aorta With Recurrent Renovisceral Ischaemia Misdiagnosed as Takayasu's Arteritis - Martin Wenkel; Kirsten de Groot; Marius Fried; Achim Neufang (EJVES Vascular Forum)
Introduction: Malignant tumours of the aorta are a rare disease and often misdiagnosed as they masquerade as wall adjacent thrombus or inflammatory disease. Due to the often delayed diagnosis and the rapidly progressing illness, the outcome is very poor. Report: A 50 year old female patient who had received coeliac and mesenteric artery stenting followed by an aortomesenteric bypass after stent occlusion two years earlier was treated. After an episode of hypertensive crisis caused by high grade stenosis of the renal arteries and review of previous tissue biopsies the diagnosis of Takayasu's arteritis was established, but the results were inconclusive. When presenting with a penetrating aneurysm of the renovisceral aorta, a complete reconstruction was performed of the renovisceral aorta due to impending rupture. Pre-operative imaging incidentally showed a sarcoma of the femur which was interpreted as an unrelated entity at the time. Finally, two years after the onset of the first symptoms, the diagnosis of an undifferentiated intimal sarcoma was established after extensive histological workup. However, the patient's condition deteriorated too quickly for her to recover as she had already developed multiple distant metastases and she died within three months of surgery. Discussion: Due to its extreme rarity, this disease is not widely recognised, even among specialists. Accordingly, the patient was initially misdiagnosed and a malignant process was not considered. An accurate diagnosis at the time of the first open surgery might have presented the opportunity for radical resection of the affected aorta. Unfortunately, there are no non-invasive tools available to diagnose intimal sarcoma and, given the rapid progression of the disease, the prognosis remains poor, with a survival of only a few months.